Putting things in context: the effect of corporate venture capital investments on the market for ideas - Jacobs, Charlotte (2019)
This PhD dissertation (Tese de Doutorado) critically reviews extant research on CVC investments and suggests future paths for studies on this phenomenon. The empirical study included in this dissertation, already puts one of these suggestions in practice. Whereas former research has mainly focused on the consequences of CVC investments on either the corporate investor or the CVCbacked entrepreneur, we empirically analyze the effect of CVC investments on the market of ideas (innovative activity) of the technological fields where they occur. We hypothesize that initial investments in an emerging technology will positively affect the attractiveness and size of the market for ideas in this technological area. Continued CVC investments, however, will stall the influx of new inventors and reduce the size of the market for ideas. We test our hypotheses using data on the CVC investments of a sample of 73 corporate investors from the pharmaceutical, hardware, and software industry. We find that CVC investments positively affect the attractiveness of the market for ideas in the technological fields where they occur in the hardware and software industry, but not in the pharmaceutical industry. The size of the market is positively affected over the whole sample. Probing further on this relation we also analyze the moderating effect of the presence of multiple investors. This research progresses the field of research on CVC in the first place through its critical overview of the literature on this phenomenon, pointing to interesting paths to explore in the future. Secondly, our empirical research may be the start of a new avenue in this research field that up to now has restricted itself to analyzing the consequences of CVC investments for either the funder or the receiver. Moving beyond the parties directly involved, our understanding of these investments and their impact on their technological environment will be further progressed.